2015
DOI: 10.1111/jan.12875
|View full text |Cite
|
Sign up to set email alerts
|

How to ask about patient satisfaction? The visual analogue scale is less vulnerable to confounding factors and ceiling effect than a symmetric Likert scale

Abstract: The present results supported the use of visual analogue scale rather than Likert scaling in patient satisfaction surveys and stressed the need to account for as many potential confounding factors as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
222
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(235 citation statements)
references
References 49 publications
5
222
2
6
Order By: Relevance
“…The Likert scale is a form of NS, and it typically has five to seven response levels . In a study with respect to how to determine patient satisfaction, Voutilainen et al demonstrated that the VAS was less vulnerable to confounding factors and ceiling effect than a symmetric Likert scale. The ceiling effect is a measurement limitation that is observed when the majority of participants reach the maximum or near maximum score .…”
Section: Discussionmentioning
confidence: 99%
“…The Likert scale is a form of NS, and it typically has five to seven response levels . In a study with respect to how to determine patient satisfaction, Voutilainen et al demonstrated that the VAS was less vulnerable to confounding factors and ceiling effect than a symmetric Likert scale. The ceiling effect is a measurement limitation that is observed when the majority of participants reach the maximum or near maximum score .…”
Section: Discussionmentioning
confidence: 99%
“…The interventions did not improve patient satisfaction. Despite the use of visual analog scales to prevent ceiling effects , satisfaction was generally high and apparently independent of the oncologist's performance. The interventions also did not prevent decisional conflict.…”
Section: Discussionmentioning
confidence: 96%
“…The slider also suffered higher rates of non‐completion and longer completion times compared to the two other response methods. These drawbacks of sliders are in contrast to the outcomes of using the paper‐based VASs providing no difference or a quicker response time compared with the Likert‐type scales reviewed in the previous section (Funke & Reips, ; Voutilainen et al., ).…”
Section: Research Findings On Benefits and Drawbacks Of Using Continumentioning
confidence: 96%
“…While Funke and Reips () found no significant difference in response time between the use of 5‐point scales and VASs in a web survey, a study conducted in Finland by Voutilainen, Pitkäaho, Kvist, and Vehviläinen‐Julkunen () showed positive outcomes of using a paper‐based VAS. When patients (n = 150) responded to a 5‐point Likert scale and a VAS on an 80‐mm line to express their patient satisfaction before hospital discharge, their response time with a VAS was 28% (or three and a half minutes) faster.…”
Section: Research Findings On Benefits and Drawbacks Of Using Continumentioning
confidence: 98%
See 1 more Smart Citation